SYNTHESIS AND CHARACTERIZATION OF CROSSLINKED POLYACRYLAMIDE (PAAM)-CARRAGEENAN HYDROGELS SUPERBASORBENT PREPARED BY GAMMA RADIATION - Erizal Erizal (Universitas Gadjah Mada, 2010)
A series of superabsorbent hydrogels were prepared from acrylamide and carrageenan by gamma irradiation at room temperature. Carrageenan solutions with different concentration (0.5%, 1%, 1.5%, 2%) have been blended with 5% of acrylamide and irradiated at doses 20-40 kGy. The properties of the prepared hydrogel were evaluated in terms of the gel fraction and the kinetics swelling was studied. It was found that the incorporation only 2% carrageenan (kappa) with 5% acrylamide can produces an elastic hydrogel when irradiated with gamma rays up to 40 kGy. Under optimum conditions, poly(acrylamide)-carrageenan hydrogels with gel fraction 60% and optimum swelling 250 g/g were prepared gamma radiolyticcally from aqueous solution containing 5% acrylamide and 2% carrageenan at the doses 20-40 kGy. The FT-IR spectra indicated that network of irradiated PAAM-carrageenan hydrogel was in the semi IPN structure. The hydrogels were also found to be sensitive to ionic strength of the medium, pH and temperature.